EFFECT OF EXERCISE ON OBESE STUDENTS OF HUMAN KINETICS DEPARTMENT OF ALIKO DANGOTE UNIVERSITY OF SCIENCE AND TECHNOLOGY, WUDIL, KANO (Wudil Journal of Science and Technology Education, 2025)
This study investigated the effect of exercise on obese students of the Human KineticsDepartment, Aliko Dangote University of Science and Technology, Wudil. The research adoptedan experimental design with pre-test and post-test measures. A total of 60 obese students (BMI ≥30 kg/m²) were purposively selected and divided into three groups: aerobic exercise group,resistance training group, and control group. Each intervention lasted for eight weeks. Data onbody mass index (BMI), cardiovascular endurance, and muscular strength were collected usingstandardized fitness tests. The data were analyzed using Analysis of Variance (ANOVA). Resultsrevealed significant differences among the groups in BMI reduction (F(2,57) = 8.42, p < 0.05)and cardiovascular endurance improvement (F(2,57) = 10.35, p < 0.01). Post-hoc tests showedthat aerobic exercise had the most significant effect on cardiovascular endurance, whileresistance training was more effective in improving muscular strength. The study concluded thatstructured exercise interventions significantly reduce obesity indices and enhance physicalfitness profiles. It was recommended that university health programs incorporate structuredexercise programs to combat obesity among students.
Keywords: Exercise, Obesity, Human Kinetics, ANOVA, Physical Fitness